Development of an Integrated Game Based Assessment Approach – The Next Generation of Psychometric Testing - Alina Stanciu, Cătălin Gabriel Ioniță; Dan Florin Stănescu, Adrian Toșcă (European Journal of Sustainable Development, 2019)
Game-based assessment have received a lot of attention in the last decade. In a recent study of human resources practitioners, 75% of participants indicated that they would consider using gamification as part of their own recruitment and selection strategy in the near future. Following the methodological approach previously used in educational environment, two approaches to building and using GBA in the organizational environment can be distinguished: gamified assessment – by gamifying (already existing) psychometric test; psychometric play - use of a game to gather evaluation data. Previous studies highlighted that those applying for a job are eager to use game-based assessment for self-evaluation, especially when these games are available for free. Game-based assessments can also help maintain a high commitment during the evaluation, which reduces the likelihood of some candidates dropping out in the process and also increases the amount of time that data can be collected. Current paper aim at presenting the preliminary efforts made to gamify two psychometric tests, namely spatial and verbal reasoning. Keywords: Game based assessment; recruitment; spatial reasoning; verbal reasoning